Peningkatan Pemeliharaan Kambing Peranakan Etawa (PE) sebagai Ternak Kambing Perah di Kelompok Ternak Tunas Maju Desa Setanggor - Karni, Ine; Septian, I Gede Nano; Wandira, Ica Ayu; Saedi, M. Ridwan; Aminurrahman; Amalyadi, Rezki; Anwar, Khairil; Putra, Ryan Aryadin; Gifari, Zaid Al; Nurjanah, Luluk Lailatun; Pertiwi, Eva Amalia; Firhamsah, Ikhwan; Suryadi, Muh. Aidil Fitriyan Fadjar; Dohi, Muhammad; Sadia, I Nyoman (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Peranakan Etawa (PE) goats have significant potential as dairy livestock producing high-quality milk, yet their management in the Tunas Maju Livestock Group, Setanggor Village, remains focused on meat production. The main issues include limited knowledge of dairy goat management, efficient feeding, and livestock health practices. This community service aimed to improve farmers’ skills through socialization, training on feed formulation, and livestock health management. The approach combined lectures, discussions, and practical demonstrations to strengthen applied understanding. The results indicated that farmers gained greater awareness of the potential of PE goats as milk producers, improved their knowledge of balanced feeding, and recognized the importance of animal health practices. Despite challenges in inadequate housing facilities, the program positively impacted farmers’ capacity in dairy goat management, thereby supporting community welfare and strengthening the local economy